A PRIMEIRA REPÚBLICA NA “CIDADE DOS BISPOS” (Mariana-MG, 1889-1930) - Costa, Manuela Areias (Outros Tempos: Pesquisa em Foco - História, 2012)
We seek to show, within the limits of this article, some aspects of the city of Mariana, Minas Geraisduring the First Republic, an environment characterized by cultural practice dating back to the colonial past, butpermeated by appropriating new discourses,  representations and customs.  With so many significant changestaking place world and in the Brazilian situation, we suggest that social life in Mariana was in a difficultthreshold setting,  the battle between the "past"  and "modern."  It is worth noting that the region possesses aunique trajectory,  inhomogeneous and full of contradictions.  Therefore,  it is to understand the limits of theappropriations and transformations of elements of modernization in the city. Furthermore, we will highlight afew aspects of the political landscape of Mariana.